The profile of thyroid disorders in patients attending a tertiary care hospital in PoKhara, Nepal - Upadhyaya, Tirthalal; Sapkota, Raju (Journal of Diabetes and Endocrinology Association of Nepal, 2019)
Background: The profile of thyroid disorder has been reported with limited evidence in Nepal. The aim of this study was to examine the profile and incidence of different types of thyroid disorder in patients attending a hospital appointment in Western Nepal and identify factors associated with it. Method: This was a hospital-based study. A total of 1000 patients attending the department of medicine at Gandaki Medical College, Teaching Hospital and Diabetes, Thyroid and Endocrinology Care Centre, Pokhara for thyroid examination were recruited. Thyroid disorders were classified as hypothyroidism, Hyperthyroidism, T4-thyrotoxicosis including their sub types where applicable. Results: Nearly 33% of the participants were found to have some form of thyroid disorders. Majority of the patients with thyroid disorder were females (87%). Hypothyroidism was found to be the most common type of thyroid disorder (57.5%) followed by hyperthyroidism (37.5%) and secondary hyperthyroidism (5.0%). BMI was found to be independently associated with hyperthyroidism on regression model. Conclusion: Hypothyroidism was found to be the most common thyroid disorder followed by hyperthyroidism. The findings highlight that thyroid disorder is a significant clinical burden and a major public health concern in Western Nepal. The findings also emphasise a need to roll out thyroid screening programmes in the general population so that this condition can be identified and treated early.